Meningkatkan Harga Diri Pasien Kusta Dengan Terapi Kelompok - Fajar Rinawati; Moh Alimansur (Akademi Keperawatan Dharma Husada Kediri, 2016)
Leprosy is a chronic infectious disease that can cause disability. East Java is the province where leprosy cases are evident in Indonesia. Negative stigma on people with leprosy can cause serious psychosocial problems, one of them is low self esteem. The purpose of this study was to identify the effects of group therapy toward self esteem of patients with leprosy. The design of this study was quasy-experimental design with one group intervention with total sampling method. The sample of this study ware patients in inpatient care (14 respondents). The results showed that there were significant differences of self esteem between before and after intervention (p-value=0,033). Patients with leprosy need to change their negative perception in order to be able to adapt positively. Keywords: supportive group, self esteem, leprosy